Portable cardiac self-stress test device development based on metabolic equivalent (MET) - Whomaira binti Abdul Samad; Mohd Afzan bin Othman; Norlaili binti Mat Safri; Mohd Azhar bin Abdul Razak (Institute of Advanced Engineering and Science, 2019)
Cardiovascular disease (CVD) is the main cause of death worldwide and the type varies depending on symptom and causes. There are several procedures to determine the type of CVD such as blood test, holter monitoring, cardiac stress test and many more. Cardiac stress test is a procedure to exert pressure on the heart by doing physical activities to determine heart functionality and abnormal heart activity. It is done to gather information on heart condition supported by evidence in the form of electrocardiogram (ECG) signal. However, patients with heart problem will have to take turns to run the test due to limited access to the equipment especially in government hospital. Therefore, this paper proposed the development of cardiac self-stress test device to provide a pre-diagnosis result based on metabolic equivalent (MET) value. The device named “i-STress device” is a stand-alone device integrating the use of software application and hardware. The software was built by using MIT App Inventor 2 and the hardware built based on Arduino 101 and Sparkfun Heart Monitor AD 8232 and the test result saved in SD card. The device will be useful to sort out patient’s case priority as well as providing pre-diagnosis result before conducting a real cardiac stress test.